A Contingency Framework for the Performance Consequences of Team Boundary Management: A Meta-analysis of 30 Years of Research - Leicht-Deobald, Ulrich (My University, 2025)
Research suggests that teams can greatly enhance their performance through boundary manage- ment, which comprises activities that establish, maintain, and regulate linkages with the sur- rounding environment. However, such performance gains do not materialize equally in all instances, and some teams struggle to benefit from boundary management. Integrating insights from social network and team-level resource allocation theories, we develop a contingency framework that considers the internal organization of a team’s boundary management (i.e., the carrier, target, and type of such activities) as a key moderating factor that accounts for the varying effects. To test this framework, we use a meta-analytic approach that synthesizes >30 years of empirical research (i.e., 85 primary studies covering 10,848 teams). Our results show a positive main effect of team boundary management on team performance. Crucially, these performance benefits are more pronounced when the target of boundary management is extraorganizational rather than inside the home organization and when the type of boundary management activities is boundary spanning (e.g., coordination, representation, or information search) rather than boundary strengthening (e.g., buffering, guarding, or sentry activities). Moreover, boundary management is more effective when executed by formal team leaders rather than team members, and our results tentatively suggest that this may reflect differences in effectiveness between leaders and members in boundary strengthening, rather than boundary spanning. Overall, our findings advance theory on team boundary management by clarifying pre- viously ambiguous findings and illustrating how teams can design their boundary management activities to be most effective.
PUBLISHED
Keywords: Meta-analysis; Team effectiveness; Team performance; Team boundary work; Team boundary management; Team boundary spanning; Digital Engagement; Identities in Transformation; Inclusive Society; Human Resource Management; Innovation; International Business; Leadership; Organisation design, development, theory, behaviour